Faktor Risiko Hipertensi Pada Masyarakat Usia Dewasa & Lansia Di Tambaksari Surabaya - Putri, Linta Meyla; Mamesah, Marline Merke; Iswati, Iswati; Sulistyana, Caturia Sasti (Journal of Health Management Research; Vol 2 No 1 (2023): Journal of Health Management Research, 2023)
Background: Surabaya city has a high rate of hypertension, one of the region which has highest incidents of hypertension is Rangkah, Tambaksari. The number of hypertension incidents in Tambaksari placed 5 th ranks of region which has largest hypertension incidents. Aims: The aim of this study is to analyze the risk factors for hypertension in Rangkah Village, Tambaksari District, Surabaya City Methods: Discriptive analytical research using cross sectional approach. The sample in this study were 44 respondents. Results: The majority of respondents who were at high risk of hypertension are women (60%), pre-adult age group (46%), have primary school education (36.2%), have jobs in the private sector (46%) with the majority of income > IDR. 2,000,000,- . There were significant relationship between nutritional status (p-value= 0.000; OR=3.097), physical activities (p-value= 0.031, OR=1.582), large coffee consumption (p-value= 0.037, OR=1.537), and stress (p-value = 0.031, OR = 1.582) with the risk of hypertension in the Rangkah area, Tambaksari, Surabaya City. Conclusion:  There were significant relationship between nutritional status, physical activities, heavy coffee consumption and stress with the risk of hypertension in the Rangkah area, Tambaksari, Surabaya City.